ANALISIS PENGGUNAAN APLIKASI HANPING CHINESE DICTIONARY LITE TERHADAP PENGUASAAN KOSAKATA BAHASA MANDARIN PADA MAHASISWA KELAS A ANGKATAN 2019 PENDIDIKAN BAHASA MANDARIN FKIP UNTAN - Irwandi, Mimi; Ina, Ina; Lusi, Lusi (Universitas Tanjungpura, 2023)
Vocabulary plays a vital role in every language. At present, many educational media are developed as auxiliary tools for language learning, such as Hanping Chinese Dictionary Lite. Hanping Chinese Dictionary Lite is an electronic dictionary that can help learners learn Chinese vocabulary. This study aims to understand the efficiency of students using the Hanping Chinese Dictionary Lite and students' evaluation of the Hanping Chinese Dictionary Lite. This study uses three research methods: test method, questionnaire survey method, and interview method. The results of the test and questionnaire survey show that the use of Hanping Chinese Dictionary Lite can effectively improve students' Chinese vocabulary. Because after using the dictionary software, the student's mastery of Chinese language has improved, that is, the result of the test is 60% and the result of the questionnaire is 53.50%. In the learning process, the author adopts six steps: showing the mobile phone dictionary to the students, conducting a pre-test, implementing the mobile phone dictionary, conducting a post-test, conducting a questionnaire survey, and conducting interviews. The final results of the interviews show that the evaluation of the dictionary software by the students is very good. It can be said that the students are satisfied with the use of the Hanping Chinese Dictionary Lite and think it is worth using the software.